Toward an Effective Combination of multiple Visual Features for Semantic Image Annotation - B. Minaoui; M. Oujaoura; M. Fakir; M. Sajieddine (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
In this paper we study the problem of combining low-level visual features for semantic image annotation. The problem is tackled with a two different approaches that combines texture, color and shape features via a Bayesian network classifier. In first approach, vector concatenation has been applied to combine the three low-level visual features. All three descriptors are normalized and merged into a unique vector used with single classifier. In the second approach, the three types of visual features are combined in parallel scheme via three classifiers. Each type of descriptors is used separately with single classifier. The experimental results show that the semantic image annotation accuracy is higher when the second approach is used.